Plan de negocios para la creación de un centro de asesoramiento para la competitividad empresarial (cace) dirigida a las pequeñas y medianas empresas de la ciudad de Babahoyo - Valverde Arana, Gustavo José (2011)
In the current world CHANGES so astonishing are being presented and to such a speed of time that their implications are relentless for our professional and managerial life. transformations that could not imagine make some years, months or you grieve behind weeks they are happening in a vertiginous way. In these moments this changes are generated with such a grade of INTENSITY and VOLATILITY that truly enrich the opportunities for the humanity, the countries, the organizations and it stops each one of us. Inside the content of the present thesis we will develop the following content according to the established chapters.......